THE GROUNDS OF CLARITROMYCIN USE IN THE TREATMENT OF PSORIASIS - V. L. Rybkina (Медицинская иммунология, 2014)
Abstract. Claritromycin influence on the keratinocytes proliferation and differentiation and lymphocytes proliferation and clasters of differentiation expression in vitro was investigated. It was established that claritromycin in dose 2 mkg/ml inhibited psoriatic keratinocytes proliferation and increased its differentiation degree in culture. Claritromycin influence was mediated by CD4+ lymphocytes. Furthermore, claritromycin in vitro decreased the number of СD25+ lymphocytes and spontaneous and PHA-induced lymphocytes proliferation for psoriatic patients. These data allow to include claritromycin in the treatment regimen of psoriasis.